The reliability of the WAnT-Swim, a novel laboratory-based, swim-specific anaerobic capacity test performed using a swimming ergometer - Holohan, J. D.; DeBlois, J. P.; Brutsaert, T. D. (Measurement in Physical Education and Exercise Science, 2024)
Anaerobic capacity is an important determinant of swimming performance, and a feasible land-based test for measuring swim-specific anaerobic capacity is lacking. This study assessed the test-retest reliability of a swim-specific modification of the Wingate anaerobic capacity test: the WAnT-Swim. Ten competitive and fitness swimmers from the local college community completed four WAnT-Swim tests, two per day on two separate days, to determine peak, mean, and low power, as well as fatigue index (FI). Reliability was assessed using coefficients of variation (CV), intraclass correlation coefficients (ICC), and Pearson correlations. Power output exhibited low CV (<6%) with excellent reliability (ICC =0.98) and strong associations between tests (r = .92). FI demonstrated the weakest reliability (CV = 3.9 ± 1.0%; ICC = 0.65; r = .13). These data suggest that the WAnT-Swim, when administered using the VASA swimming ergometer, is a reliable test of anaerobic power during land-based swimming.